Shrinkage vectors and volumetric shrinkage percentage of differently applied composites. (March 2021) - Kaisarly, Dalia; El Gezawi, Moataz; Rösch, Peter; Kunzelmann, Karl-Heinz
Abstract: Bulk-fill composites can be placed at a thickness of 4 mm due to their sufficient depth of cure. The aim of this study was to investigate the effects of bulk versus incremental application methods on the shrinkage vectors and the percentage of volumetric polymerization shrinkage of the composites. Twelve molars were divided into three groups (n = 4), and cylindrical cavities (diameter = 6 mm, depth = 4 mm) were prepared, etched and bonded with OptiBond FL (Kerr). Cavities were restored with a 4-mm bulk-fill composite of Tetric EvoCeram Bulk Fill (TBF, Ivoclar Vivadent) designated as "TBF-bulk", with two 2-mm increments of a bulk-fill composite designated as "TBF-incremental", and with two 2-mm increments of a hybrid composite Tetric EvoCeram (TEC, Ivoclar Vivadent) designated as "TEC-incremental". Each material application was scanned twice in a micro-CT (uncured and cured states), and inherent air bubbles served as markers. Scans were subjected to image segmentation to calculate the shrinkage vectors and the percentage of volumetric polymerization shrinkage. Significantly greater mean values of the shrinkage vectors were observed in "TBF-bulk", followed by "TBF-increment1", with no difference between the remaining increments of the groups (ANOVA, Tamhane's T2, p < 0.001); the percentage of volumetric polymerization shrinkage did not differ among the groups (ANOVA, Tamhane's T2, p = 0.759). Bulk application resulted in greater shrinkage vectors than in the incremental applications, despite the volumetric evaluation displaying no difference regarding the application methods. The discrepancy between the evaluation methods can be explained by anisotropic shrinkage, which is displayed through the shrinkage vectors but cannot be quantified by the volumetric evaluation. Incremental application of resin composites remains the gold standard in class-I cavities.